Go programming language for dummies - Lee, Wei-Meng 1972- (Wiley, 2021)
Ready, set, program with Go!Now is the perfect time to learn the Go Programming Language. It's one of the most in-demand languages among tech recruiters and developers love its simplicity and power. Go Programming Language For Dummies is an easy way to add this top job skill to your toolkit. Written for novice and experienced coders alike, this book traverses basic syntax, writing functions, organizing data, building packages, and interfacing with APIs.Go...or GoLang, as it's also known...has proven to be a strong choice for developers creating applications for the cloud-based world we live in. This book will put you on the path to using the language that's created some of today's leading web applications, so you can steer your career where you want to Go!* Learn how Go works and start writing programs and modules* Install and implement the most powerful third-party Go packages* Use Go in conjunction with web services and MySQL databases* Keep your codebase organized and use Go to structure dataWith this book, you can join the growing numbers of developers using Go to create 21st century solutions. Step inside to take start writing code that puts data in users' hands
Get going with one of today's top languages!This book walks with you as you take your first steps in the fast-growing coding language, Go. You'll work through all the basics, and then you'll build job-ready skills for making applications that work in the cloud! Go is great at scooping up data from around the web and putting it into users' hands. With this book at your side you'll become adept at accessing, structuring, and serving data by writing applications that are easy to maintain and understand. Go is in high demand...this primer will put it on your resume.Inside.* Learn the fundamentals of Go* Write clean, efficient functions* Structure and organize data* Find out all about Goroutines* Discover third-party Go packages* Work with web services* Link up with REST APIs
Introduction 1; Part 1: Getting Started with Go 5; Chapter 1: Hello, Go! 7; Chapter 2: Working with Different Data Types 23; Chapter 3: Making Decisions 37; Chapter 4: Over and Over and Over: Using Loops 51; Chapter 5: Grouping Code into Functions 65; Part 2: Working with Data Structures 79; Chapter 6: Slicing and Dicing Using Arrays and Slices 81; Chapter 7: Defining the Blueprints of Your Data Using Structs 101; Chapter 8: Establishing Relationships Using Maps 113; Chapter 9: Encoding and Decoding Data Using JSON 129; Chapter 10: Defining Method Signatures Using Interfaces 151; Part 3: Multitasking in Go 163; Chapter 11: Threading Using Goroutines 165; Chapter 12: Communicating between Goroutines Using Channels 179; Part 4: Organizing Your Code 195; Chapter 13: Using and Creating Packages in Go 197; Chapter 14: Grouping Packages into Modules 211; Part 5: Seeing Go in Action 223; Chapter 15: Consuming Web APIs Using Go 225; Chapter 16: Getting Ready to Serve Using REST APIs 243; Chapter 17: Working with Databases 271; Part 6: The Part of Tens 285; Chapter 18: Ten Useful Go Packages to Create Applications 287; Chapter 19: Ten Great Go Resources 299; Index 303
Keywords: Natur, Technik